中国植物油料进口依赖及进口安全研究 Import dependence and import safety of oilseeds in China - 曹冲1，2，杨桔1，袁国军1，2 CAO Chong1,2，YANG Ju1，YUAN Guojun1,2 (Zhongguo youzhi)
在百年未有之大变局的背景下，保障植物油料进口稳定对中国植物油料安全有着深远的影响。在分析中国植物油料生产与贸易的基础上，刻画其进口增长的特征以及考察其进口的变化趋势，并对植物油料进口的依赖程度及进口安全进行探讨。结果表明：中国植物油料进口依然保持较高水平；中国植物油料自给率不断下降，对进口的依赖程度相对较高；中国植物油料的进口来源地主要集中在巴西和美国，且较高的植物油料进口依赖程度使得中国植物油料进口安全水平较低。因此，提出了提高植物油料综合保障能力，做好植物油料进口和储备调节，发展植物油料进口市场多元化等建议。 Under the background of great changes unprecedented in a century, ensuring the stability of oilseeds import has a far-reaching impact on the safety of oilseeds in China. On the basis of analyzing the production and trade of Chinese oilseeds, the characteristics of its import growth was described and the changing trend of its import was examined. The import dependence and import safety of oilseeds were discussed. The results showed that the import of oilseeds in China remained at a high level; the self-sufficiency rate of oilseeds in China was declining and the dependence degree on imports was relatively high; the import sources of oilseeds in China were mainly concentrated in Brazil and the United States, and the high dependence degree on imports made the safety level of oilseeds low. Therefore, some suggestions were put forward, such as improving the comprehensive guarantee capacity of oilseeds, improving the adjustment of oilseeds import and reserve, and developing the diversification of oilseeds import market.